Solving Capacitated Vehicle Routing Problem (CVRP) Using Tabu Search Algorithm (TSA) - Ibrahim Obaid, Omar (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
This paper investigates the capacitated vehicle routing problem (CVRP) as it is one of the numerous issues that have no impeccable solutions yet. Numerous scientists in the recent couple of decades have set up various explores and utilized numerous strategies with various methods to deal with it. However, for all researches, finding the least cost is exceptionally complicated. In any case, they have figured out how to think of rough solutions that vary in efficiencies relying upon the search space. Furthermore, tabu search (TS) is utilized to resolve this issue as it is fit for solving numerous complicated issues. The algorithm has been adjusted to resolve the exploration issue, where its methodology is not quite the same as the normal algorithm. The structure of the algorithm is planned with the goal that the program does not require a substantial database to store the data, which accelerates the usage of the program execution to acquire the solution. The algorithm has demonstrated its accomplishment in resolving the issue and finds a most limited route.